Consumption of fig fruits grown in Oman can improve memory, anxiety, and learning skills in a transgenic mice model of Alzheimer's disease. (12th December 2016) - Subash, Selvaraju; Essa, Musthafa Mohamed; Braidy, Nady; Al-Jabri, Ahood; Vaishnav, Ragini; Al-Adawi, Samir; Al-Asmi, Abdullah; Guillemin, Gilles J.
Abstract : Alzheimer disease (AD) is one of the most common forms of dementia in the elderly. Several reports have suggested neurotoxic effects of amyloid beta protein (Aβ) and role of oxidative stress in AD. Figs are rich in fiber, copper, iron, manganese, magnesium, potassium, calcium, vitamin K, and are a good source of proanthocyanidins and quercetin which demonstrate potent antioxidant properties. We studied the effect of dietary supplementation with 4% figs grown in Oman on the memory, anxiety, and learning skills in APPsw/Tg2576 (Tg mice) mice model for AD. We assessed spatial memory and learning ability, psychomotor coordination, and anxiety-related behavior in Tg and wild-type mice at the age of 4 months and after 15 months using the Morris water maze test, rota-rod test, elevated plus maze test, and open-field test. Tg mice that were fed a control diet without figs showed significant memory deficits, increased anxiety-related behavior, and severe impairment in spatial, position discrimination learning ability, and motor coordination compared to the wild-type control mice on the same diet, and Tg mice fed on 4% fig diet supplementation for 15 months. Our results suggest that dietary supplementation of figs may be useful for the improvement of cognitive and behavioral deficits in AD.